EDUCATION AND GENDER - Asri Yuni vikasari; Anis Fauzi (Media Inovasi Pendidikan dan Publikasi, 2023)
Education with a gender perspective is an effort to equalize women and men in fulfilling their rights, roles, responsibilities and activities in social life. In general, the view of society is that women are under the power of men in social life. The method used in writing this article is qualitative, the author explores in-depth information about education and gender. The approach used is library research or library research. Writing this article aims to explain the concept of education with a gender perspective, the causes of gender inequality and gender equality efforts in the world of education.